Adoption of Ifrs in an Emerging Market: The Chilean Case [Adopción de Ifrs en Una Economía Emergente: El Caso de Chile] - Espinosa-Mendez, C (Emerald Group Publishing Ltd., 2015)
PurposeThe purpose of this paper is to analyze the impact triggered by adopting International Financial Reporting Standards (IFRS) in South America. In order to do this, the case of Chile is considered, as it was the first country in the region to adopt IFRS in full form from 2009. Design/methodology/approachThe authors analyze a sample of 43 Chilean companies. The analysis has two stages. First, the authors analyze if the adoption of IFRS in Chile produced a statistically significant change in the main financial indicators. Then, the authors analyze the market reaction to the announcement of the adoption and implementation of IFRS, by doing an event study. FindingsThe authors found that adopting IFRS in Chile produced a statistically significant change in the main financial indicators, except for in leverage and Price-Earnings Ratios. As for the main accounts of the financial statements, the authors found significant differences, with the exception of inventories and current assets. However, after assessing the market reaction to the announcement of the adoption and implementation of IFRS, by studying the events, the authors report neither reward nor punishment by the market. Originality/valueThis paper pioneers the analysis of the impact triggered by adopting IFRS in South America. The authors results apply not only to Chile but also to a number of South American countries since many of these countries share similar characteristics with Chile. © 2015, © Emerald Group Publishing Limited.